The Role of Vitamin D in Endometrial Receptivity for Successful Implantation - Nur Fadilah (Jurnal Sehat Indonesia (JUSINDO), 2026)
Successful embryo implantation depends on endometrial receptivity during the implantation window, which involves gene regulation, decidualization, and local immune modulation. Vitamin D has received attention due to the expression of the vitamin D receptor (VDR) in the endometrium and its role in regulating receptor gene transcription. To review the scientific evidence regarding the association of vitamin D levels with endometrial receptivity and implantation outcomes in assisted reproductive technology (ART). A literature review was conducted through a systematic search of PubMed, Google Scholar, and ScienceDirect (2020–2026). Observational human studies assessing vitamin D levels on endometrial parameters or pregnancy outcomes were included; eight studies met the criteria. Vitamin D plays a role in the regulation of HOXA10, HAND2, decidualization, and the tolerogenic immune balance. However, clinical outcomes are heterogeneous; some studies show benefits primarily in deficiency states, while others find no significant associations with implantation rate or live birth rate. Vitamin D has the potential to be a permissive factor in endometrial receptivity, but it is not a primary determinant of implantation success.